Assessment of e-learning continuance usage in higher education institutions : a case study of IIUM - Usman, Ibrahim Shehu (Kulliyah of Information and Communication Technology, International Islamic University Malaysia, 2014)
The use of information and communication technology (ICT) is believed to be one of the most crucial developments in higher educational institutions as it touches every aspect of the education sector. This technological breakthrough has led to the emergence of e-learning services, which in recent time has become popular globally. IIUM is one of the universities that adopted e-learning system in Malaysia. Adoption of e-learning is a very important issue in an educational institution like IIUM, but the most important is the user's continuance intention towards the using it. This study takes a cross sectional analysis of determinants of e-learning continuance intention using the Expectation Confirmation Theory (ECT) as the research framework. The data collected in this study was based on 178 responses, collected from eight Kulliyahs (Faculties) of IIUM. The adapted and modified questionnaires were designed using the 5-point Likert scale and the Cronbach Coefficient Alpha was used to test the internal consistency of research instruments. Linear Simple and Multiple Regressions were employed to determine the relationships between the variables. A number of relationships were identified in this study. Among others is the positive influence of perceived performance, usability and satisfaction on the continuance intention of using e-learning system. A set of recommendations is provided to assist education sector and IIUM in particular in enhancing and sustaining the e-learning technologies so as to provide students with greater advantages.